Conception of a 3D Metamaterial-Based Foundation for Static and Seismic Protection of Fuel Storage Tanks - La Salandra, Vincenzo; Wenzel, Moritz; Bursi, Oreste S.; Carta, Giorgio; Movchan, Alexander B. (Frontiers in Materials, 2017)
Fluid-filled tanks in tank farms of industrial plants can experience severe damage and trigger cascading effects in neighboring tanks due to large vibrations induced by strong earthquakes. In order to reduce these tank vibrations, we have explored an innovative type of foundation based on metamaterial concepts. Metamaterials are generally regarded as manmade structures that exhibit unusual responses not readily observed in natural materials. If properly designed, they are able to stop or attenuate wave propagation. Recent studies have shown that if locally resonant structures are periodically placed in a matrix material, the resulting metamaterial forms a phononic lattice that creates a stop band able to forbid elastic wave propagation within a selected band gap frequency range. Conventional phononic lattice structures need huge unit cells for low-frequency vibration shielding, while locally-resonant metamaterials can rely on lattice constants much smaller than the longitudinal wavelengths of propagating waves. Along this line, we have investigated 3D structured foundations with effective attenuation zones conceived as vibration isolation systems for storage tanks. In particular, the three-component periodic foundation cell has been developed using two common construction materials, namely concrete and rubber. Relevant frequency band gaps, computed using the Floquet-Bloch theorem, have been found to be wide and in the low-frequency region. Based on the designed unit cell, a finite foundation has been conceived, checked under static loads and numerically tested on its wave attenuation properties. Then, by means of a parametric study we found a favorable correlation between the shear stiffness of foundation walls and wave attenuation. On this basis, to show the potential improvements of this foundation, we investigated an optimized design by means of analytical models and numerical analyses. In addition, we investigated the influence of cracks in the matrix material on the elastic wave propagation, and by comparing the dispersion curves of the cracked and uncracked materials we found that small cracks have a negligible influence on dispersive properties. Finally, harmonic analysis results displayed that the conceived smart foundations can effectively isolate storage tanks.